Model Pembelajaran Interaktif Sebagai Upaya Implementasi Merdeka Belajar Pada Siswa SD Masa Pandemi Covid-19 - Tri Astuti; Limpad Nurrachmat; Akhmad Junaedi; Ferani Mulianingsih (Efektor, 2022)
The Covid-19 era, learning was carried out online. In the Tegal city, there are schools whose students have diverse backgrounds. They are Muslim, Christian, Hindu, Buddhist. In addition, their ethnicity is also different, some are from Java, Chinese, and Arabic. This should not be an obstacle to learning. Learning without making a fuss about differences, but in reality students still often make differences as a barrier during the learning process. The comfort of students in participating in the learning process is an important thing to strive for. These efforts can be done by applying an interactive learning model. Freedom to learn is a challenge for teachers. Students are given the freedom to develop their talents and interests without pressure. The research objectives include 1) To find out how PHB K Elementary School teachers apply interactive learning models when teaching in order to create independent learning in the classroom. 2) Barriers faced by PHB Elementary School teachers in implementing interactive learning models. This research uses a qualitative approach with the type of case study. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results showed that PHB Elementary School teachers applied an interactive learning model in order to create independent learning in students. The learning model applied is PBL and STAD. In its implementation, there are obstacles, including students who get bored easily when learning online, differences in student characteristics, teachers only get facilities from the foundation, but not from the Ministry of Education and Culture and time constraints.